Ways Forward for Tolerance-Inducing Cellular Therapies- an AFACTT Perspective - ten Brinke, Anja; Martinez-Llordella, Marc; Cools, Nathalie; Hilkens, Catharien M. U.; van Ham, S. Marieke; Sawitzki, Birgit; Geissler, Edward K.; Lombardi, Giovanna; Trzonkowski, Piotr; Martinez-Caceres, Eva (Frontiers in Immunology, 2019)
Clinical studies with cellular therapies using tolerance-inducing cells, such as tolerogenic antigen-presenting cells (tolAPC) and regulatory T cells (Treg) for the prevention of transplant rejection and the treatment of autoimmune diseases have been expanding the last decade. In this perspective, we will summarize the current perspectives of the clinical application of both tolAPC and Treg, and will address future directions and the importance of immunomonitoring in clinical studies that will result in progress in the field.